Some unexpected thermal effects on squeal events observed on the experimental bench FIVE@ECL. (November 2021) - Sinou, J-J.; Besset, S.; Lenoir, D.
Highlights: Experimental analysis of brake squeal events based on both nonlinear vibration and acoustic noise. Discussion on some unexpected thermal effects on squeal events. Links between some thermal effects and the variation of the structural behaviour of a brake system. A detailed analysis and an in-depth methodology to illustrate the thermal effects on structural analysis. Abstract: The proposed study investigates the potential links between thermal effects and structural modifications of a brake system which can lead to minor modifications of the nonlinear squeal signature at temperatures lower to 100 °C. Experiments are performed on the test bench Friction-Induced Vibration and noisE at Ecole Centrale de Lyon (FIVE@ECL). The analyses are carried out on both the vibratory nonlinear responses and the acoustic noise occurring during transient and stationary squeal events. The second main contribution is to propose a detailed analysis and an in-depth methodology to demonstrate experimentally the effects of temperature increase not only on the non-linear squeal phenomenon but also on the modal behavior of a specific part of the braking system which corresponds to the brake disc. It is shown that the characteristics of the squeal signature related to the frequencies decrease or amplitude fluctuation for specific frequencies contribution can be explained in part by a relation between temperature changes and associated structural changes in the brake system.